2014
DOI: 10.3109/01612840.2014.888602
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of the Context of Anal Sex Behavior in Ethnic Minority Adolescent Women

Abstract: Understanding the context of anal sex behavior among ethnic minority adolescent women has public health implications for behavioral sexual health promotion and risk reduction interventions. African-American (n = 94) and Mexican-American (n = 465) women (14-18 years of age) enrolled in a clinical trial completed semi-structured interviews to assess psychosocial and situational factors and relationships to sexual risk behavior, substance use, sexually transmitted infection/HIV acquisition, and violence. Bivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Our multinominal regression analysis of baseline characteristics found that Hispanic women (vs black women), women who identify as bisexual or lesbian (vs heterosexuals), women who had ever experienced both sexual and physical violence(vs no violence), and women who reported above median number of male sex partners (vs median or below) were more likely to be in the AI and VI persistors group than in the VI persistors group. These associations with longitudinal AI practice are similar to associations identified in cross-sectional studies, where AI practice has been reported as more common among Hispanic than black women, 23 28 among white compared to black women, 3 , 29 , 30 among women who have sex with both men and women, 3 , 25 , 31 , 32 among survivors of sexual 23 , 33 38 and physical violence, 33 , 39 41 and among women with multiple male sex partners. 3 , 8 , 42 , 43 …”
Section: Discussionsupporting
confidence: 83%
“…Our multinominal regression analysis of baseline characteristics found that Hispanic women (vs black women), women who identify as bisexual or lesbian (vs heterosexuals), women who had ever experienced both sexual and physical violence(vs no violence), and women who reported above median number of male sex partners (vs median or below) were more likely to be in the AI and VI persistors group than in the VI persistors group. These associations with longitudinal AI practice are similar to associations identified in cross-sectional studies, where AI practice has been reported as more common among Hispanic than black women, 23 28 among white compared to black women, 3 , 29 , 30 among women who have sex with both men and women, 3 , 25 , 31 , 32 among survivors of sexual 23 , 33 38 and physical violence, 33 , 39 41 and among women with multiple male sex partners. 3 , 8 , 42 , 43 …”
Section: Discussionsupporting
confidence: 83%
“…Numerous cross-sectional studies have identified correlates of AI among women in the U.S., finding that women who report AI are more likely to report multiple sexual partners [2,5,6], transactional sex [2,5,[7][8][9][10], lower condom use [11][12][13] and sex with both men and women [2,14]. Substance use has also frequently been found to be positively associated with AI, with AI being more common among U.S. women who report using any type of illegal drug [6,7,9,11,15,16], or binge drinking [2,10,17].…”
mentioning
confidence: 99%
“…Numerous cross-sectional studies have identified correlates of AI among women in the U.S., finding that women who report AI are more likely to report multiple sexual partners [2,5,6], transactional sex [2,5,[7][8][9][10], lower condom use [11][12][13] and sex with both men and women [2,14]. Substance use has also frequently been found to be positively associated with AI, with AI being more common among U.S. women who report using any type of illegal drug [6,7,9,11,15,16], or binge drinking [2,10,17]. Although some women do report finding AI pleasurable [18], it does seem that it may often occur under coercion or in the context of violent relationships, with women reporting AI more likely to also report rape or coerced sex [19,20], and to have experienced intimate partner physical violence [15,21].…”
mentioning
confidence: 99%